PAIR'14 / PAIR'15 STUDENT CONFERENCES ON PLANNING IN ARTIFICIAL INTELLIGENCE AND ROBOTICS - Editorial Foreword (Acta Polytechnica CTU Proceedings, 2015)
Dear Reader the original idea of the student conference on “Planning in Artificial Intelligence and Robotics” (PAIR) is to join young researchers from particular laboratories in Czech Republic, where planning problems are investigated from artificial intelligence (AI) or robotics points of view. The first year of PAIR has been organized at the Dept. of Computer Science, Faculty Electrical Engineering, Czech Technical University in 2014. At PAIR 2014, laboratories from Prague and Brno were presented. In particular, students and researchers from Charles University, Czech Technical University in Prague, Brno University of Technology, and Central European Institute of Technology participated at the event. Beside an introduction of the particular research groups and their topics, students presented contributions on their current research results. Ten papers were presented on topics ranging from domain–independent planning, trajectory planning to applications for unmanned aerial and legged robots. This first event provides us an initial experience with the community of young researchers in Czech Republic that are working planning in robotic or AI. Based on the success of PAIR 2014, we decided to continue with our effort to establish a suitable fora for students that are geographically very close, but usually do not meet, because of participation on different Robotics and AI events. The second student conference on Planning in Artificial Intelligence and Robotics (PAIR 2015) successfully continues the tradition of the first year of the conference organized in Prague. This year, the conference was collocated with 10th anniversary of RoboTour contest in Písek. This format enable us to extend the impact of the PAIR conference and improve the visibility of the growing student community. The conference reached a good amount of interesting papers focused on image processing for mobile robots, swarm control, driving simulation, robot control, or domain–independent multi–agent planning in contrast to vision–based planning and routing optimization. The format of the conference proves to be very vital and interesting for the young researchers community. In this year, we have got an international attendance, great opportunity to host RoboTour workshop, and very positive feedback and interest of international young research community. We would like thank to Jan Najvárek for his interesting invited talk on the topic of RoboAuto. We believe the PAIR tradition will continue to the third year with increasing interest and growing community. We thank all the authors for high quality presentations and final versions of the articles presented in this proceedings. Thank you all, J. Faigl and J. Vokřínek Editors